Indifference, resistance, possibility: Probation staff perspectives on the introduction of professional registration - Millings, Matthew (Probation journal, 2025)
Rehabilitating Probation is a three-year research project (2022–2025), exploring the most recent iteration of probation reform in England and Wales. This article takes as its focus the responses from interviews with a mixed sample of probation staff in one case study region (n = 56) to questions they were asked about their knowledge of the Professional Register and what implications they felt it would have for their careers. Our sweep of interviews, running from March 2024 through to September 2024, captures the views of staff in the months leading up to the formal establishment of the Professional Registration policy framework that set out the requirements and guidance for probation staff around professional registration, probation professional registration standards, and loss of authority to practice. Our findings suggest that although some staff in our sample expressed a cautious support for professional registration, there was also a high level of indifference – and in some cases resistance - among those interviewed suggesting a need to articulate more clearly what the purpose of Professional Registration is and what its implementation means for those working within the Probation Service.